2014
DOI: 10.15361/2175-0106.2014v30n1p32-37
|View full text |Cite
|
Sign up to set email alerts
|

ATIVIDADE ANTIBIOFILME DE DITERPENO ISOLADO DE Croton antisyphiliticus FRENTE Staphylococcus aureus.

Abstract: RESUMOO presente estudo teve como principal objetivo avaliar o potencial de atividade antimicrobiana de diterpeno isolado de Croton antisyphiliticus, espécie nativa do Cerrado, frente biofilme de Staphylococcus aureus, isolados do leite de animais com mastite. O diterpeno ácido ent-kaur-16-en-18-óico foi avaliado quanto à capacidade de erradicação da biomassa e também à redução da população bacteriana sob o biofilme. O antibiótico sulfato de gentamicina foi utilizado como tratamento comparativo. A atividade an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…(2013) reported that tannins from medicinal plant may prevent the formation of biofilms. The diterpene isolated from the Croton antisyphiliticus root chloroform extract was not able to completely reduce biofilms, but efficient inhibitory activity was found, capable of promoting significant antibiofilm activity by eliminating 56% S. aureus at 250 µg/ml (Nader et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2013) reported that tannins from medicinal plant may prevent the formation of biofilms. The diterpene isolated from the Croton antisyphiliticus root chloroform extract was not able to completely reduce biofilms, but efficient inhibitory activity was found, capable of promoting significant antibiofilm activity by eliminating 56% S. aureus at 250 µg/ml (Nader et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The disinfectants and antibiotics ineffectiveness have been related to bacterial biofilm formation in food industry (Mafu et al., 2011; Simões et al., 2010), conducting pathogens to consumers and causing outbreaks of foodborne illnesses (Chmielewski and Frank, 2003). Bacterial cells in biofilms can be up to 1000 times more resistant to antibiotics and sanitizing agents (Nader et al., 2014). Due to the difficulties to reduce cells adhered to surfaces, new strategies for the biofilm control have been studied (Donlan, 2002), such as plants containing flavonoids that may break outer membrane and inhibit bacteria enzymatic activity (Nascimento et al., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The ineffectiveness of disinfectants and antibiotics has been frequently related to bacterial biofilms (Mafu et al, 2011), because the biofilms cells are up to 1,000 times more resistant to these antimicrobial agents (Nader et al, 2014). Due to the difficulties in reducing bacteria in biofilms, new control strategies have been evaluated (Donlan, 2002).…”
Section: Determination Of Minimum Inhibitory Concentration (Mic) and ...mentioning
confidence: 99%